Improvement of Cadres' Skills and Knowledge to Provide Comprehensive Health Services for the Elderly - Djuari, Lilik; Dewanti, Linda; , Sulistiawati; Brilianti, Natasya Nurvita; Nurdiansyah, Farhan; Prajitno, Subur (Folia Medica Indonesiana, 2023)
Highlights: Due to the increasing elderly population in Indonesia, this study must address the knowledge and skill gaps among health cadres in a number of Integrated Health Posts for the Elderly (Pos Layanan Terpadu Lanjut Usia/ Posyandu Lansia). Through this study, the health cadres increased their knowledge and skills, enabling them to provide comprehensive health services for the elderly. Abstract Numerous issues have arisen as a result of the large size and rapid growth of the elderly population, attesting to the need for serious efforts from all sectors to enhance their welfare. However, the health cadres at the Integrated Health Post for the Elderly (Pos Layanan Terpadu Lanjut Usia/ Posyandu Lansia) lacked the training that would have equipped them with the necessary knowledge and skills to carry out their duties. This study aimed to evaluate the significance of training for enhancing the cadres' knowledge and skills in providing comprehensive health services for the elderly. This study was quasi-experimental research with a pre-test and post-test design. The data analysis was performed using the Shapiro-Wilk test (p>0.05) and the Wilcoxon test (p<0.05). A total of 30 health cadres at Songgon Community Health Center were measured for their levels of knowledge and skills before and after the training. The training included filling out health evaluation charts, providing leaflets containing health counseling materials for the elderly, practicing exercise for the elderly, and singing an elderly marching song. Before filling out the health evaluation chart, the cadres had to measure the elderly's degree of independence as well as their mental, emotional, and nutritional status. The cadres also had to measure the weight, height, and blood pressure of the elderly. Prior to training, the cadres' knowledge of hospitalization referrals, independence, and physical exercise for the elderly was limited. The cadres' skills in filling out health evaluation charts, assessing mental, emotional, and nutritional status, measuring blood pressure, and instructing physical exercise were also inadequate. There was a significant difference in the knowledge and skills of the health cadres before and after training (p<0.05). In conclusion, there was an improvement in the health cadres' knowledge and skills regarding comprehensive health services for the elderly at the Posyandu Lansia.